Applications of photochemical techniques to imaging of surfaces and nanoparticles - Laferriere, Marie (University of Ottawa (Canada), 2006)
Highly energetic 157 nm laser irradiation was explored for possible use in the nanolithographic process; 157 nm irradiation of photoresists containing photoacid generators (PAG) was shown to generate acid as it does at longer wavelengths. Irradiation of polymers films that did not contain a PAG was also shown to generate acid but required a higher exposure dose. These polymer films were also shown to generate HF upon 157 nm irradiation. Experiments in solution have shown that 1,1,1,3,3,3-hexafluoro-2-propanol could trap electrons with a rate constant of 6.6 x 1010 M-1s -1. Electrons would be generated by the non-fluorinated moieties of the polymer film upon 157 nm irradiation and subsequently trapped by the fluorinated moieties leading to the release of fluoride, deprotonation at the ionization site would lead to HF formation. Laser flash photolysis of films with 157 nm as the excitation wavelength was attempted, this experiment was technically very challenging because of the high absorbance of most organic compounds, water and oxygen at 157 nm. However, a triplet absorbance for xanthone in perfluorononane was detected. TEMPO and 4-amino-TEMPO were shown to quench the fluorescence of CdSe quantum dots covered with tri-octylphosphine oxide (TOPO). The quenching is size-dependent, being more efficient for the smaller than for the larger quantum dots. Furthermore, 4-amino-TEMPO is more efficient at quenching the fluorescence of quantum dots than TEMPO. Stern-Volmer plots for the quenching of quantum dots by TEMPO are upward curving, indicating distance dependent quenching. The Perrin model was used to analyse the results. 4-Amino-TEMPO was shown to form complexes with quantum dots by electron spin resonance spectroscopy. Downward curving Stern-Volmer plots for fluorescence quenching by 4-amino-TEMPO (4AT) indicate that 4AT may first bind in openings in the TOPO ligand shell and subsequently bind by displacing the TOPO ligands. Prefluorescent probes were developed. The fluorescence of the 4AT-quantum dot complex was restored in the presence of photogenerated radicals from azobisisobutyronitrile (AIBN). UV irradiation of polymer films containing quantum dots was shown to enhance the fluorescence of quantum dots. Quenching by TEMPO and 4AT of quantum dots and subsequent quantum dot fluorescence recovery in channels of photonic crystal fibres was recorded by fluorescence imaging. It is explained by the non-linear quenching observed in solution and by the diffusion of the quantum dot and the quencher in the channels of the photonic crystal fibres.
Keywords: Chemistry, Physical.